Keanekaragaman Serangga Hama dan Musuh Alami pada Pertanaman Kacang Hijau (Vigna radiata) di Desa Lakekun Kecamatan Kobalima Kabupaten Malaka - Fransiska Manek; Titik Sri Harini; Petronella S. Nenotek (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This research was conducted in Lakekun Village, Kobalima District, Malaka Regency from May to July 2023, aiming to determine the types of insect pests and natural enemies in mung beans. Data collection was carried out using direct observation techniques on mung bean plants and sampling using several traps. The types of traps used were pitfall trap, swepnet, yellow sticky trap, swing net and light trap. Sampling was done diagonally to determine the sample unit. The number of observation plots in the field is 3 observation plots. in 1 plot there are 5 sample units and a total of 3 observation plots there are 15 aub plots observed. Insect pests found on mung bean in the research location have three roles, namely as pests, predators and parasitoids. Species that act as pests consist of Artherigona exigua, Nezara viridula L, Aphis craccivora, Halyomopha halys, Riptortus linearis, Adoretus sp. and Gralliclava horrens. Insects that act as predators consist of Menochilus sexmaculatus, Coccinella transversalis, Orthhetrum sabina, Iscunara senegalensis. While insects that act as parasitoids are Tiphia femorata. The highest population found at the research site was Aphis craccivora which amounted to 315 individuals and the lowest population was Graliclava horrens with a total of 7 individuals. The value of the diversity index in mung bean plants is classified as moderate, namely 1.89. Keywords: diversity, insects, mung bean, identification.